An efficient biotransformation of dialkyl esters of 2-oxoglutaric acid by Rhodotorula minuta whole cells - Rustoy, Eduardo Miguel (2008)
Whole cells of the yeast Rhodotorula minuta were used in the biotransformation of dialkyl esters of 2-oxoglutaric acid. Almost 100% of conversion with 97-98% of enantiomeric excess of the (S) form of 2-hydroxydiesters was obtained through an enantioselective reduction of dimethyl and diethyl 2-oxoglutarate. When longer alkoxy chain 2-oxoglutarates were used as substrates, the corresponding 4-hydroxybutyric esters were obtained, suggesting a combination process including hydrolysis, decarboxylation and reduction. The cells showed a remarkable high productivity: high conversion and enantiomeric excess were obtained at 2 g wet weight mmol-1 substrate.